Ubiquitin specific peptidase Usp53 regulates osteoblast versus adipocyte lineage commitment - Hadla Hariri (Nature Portfolio, 2021)
Abstract We have previously shown that parathyroid hormone (PTH) induces the phosphorylation of the DNA-binding protein Nascent polypeptide associated complex And Coregulator alpha (NACA), leading to nuclear translocation of NACA and activation of target genes. Using ChIP-Seq against NACA in parallel with RNA-sequencing, we report the identification of Ubiquitin Specific Peptidase 53 (Usp53) as a target gene of PTH-activated NACA in osteoblasts. A binding site for NACA within the ChIP fragment from the Usp53 promoter was confirmed by electrophoretic mobility shift assay. Activity of the Usp53 promoter (− 2325/+ 238 bp) was regulated by the JUN-CREB complex and this activation relied on activated PKA and the presence of NACA. Usp53 knockdown in ST2 stromal cells stimulated expression of the osteoblastic markers Bglap2 (Osteocalcin) and Alpl (Alkaline phosphatase) and inhibited expression of the adipogenic markers Pparg and Cebpa. A similar effect was measured when knocking down Naca. During osteoblastogenesis, the impact of Usp53 knockdown on PTH responses varied depending on the maturation stage of the cells. In vivo implantation of Usp53-knockdown bone marrow stromal cells in immunocompromised mice showed an increase in osteoblast number and a decrease in adipocyte counts. Our data suggest that Usp53 modulates the fate of mesenchymal cells by impacting lineage selection.